Migrants in high medieval Bohemia. Issue 3 (27th May 2019) - Hardt, Matthias
ABSTRACT: In the High Middle Ages, Bohemia witnessed migration which had a lasting effect on settlement, the landscape and the demographic and social structure of the population. At first, long-distance traders came to Prague, to whom the Přemyslid rulers granted the privilege of living according to the lex et iustitia Theutonicorum, probably from the end of the eleventh century. In the thirteenth century, many urban and rural settlements following the ius Theutonicum were established and often granted the rights of Magdeburg. These included the right to inherit real property, and an incentive both for immigrants from German areas and for the Czech population to participate in the foundation of new cities and settlements, in restructuring the Bohemian landscape and increasing production especially of cereals. In the fourteenth century, Prague and other cities saw immigration by the Czech rural population, eventually leading to the Czech language dominating in urban settings as well.